2020
DOI: 10.1111/aje.12809
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the status and distribution of pangolins in Togo (West Africa)

Abstract: Pangolins are considered among the most threatened mammal species, both globally and also in Africa. However, almost nothing is known on their status and distribution across wide areas of their range, particularly in West African countries. Here, we assess the status and distribution of pangolin species in Togo. Fieldwork was carried out in five localities around the Fazao Malfakassa National Park, five sites around the Togodo Protected Areas Complex (Togodo North and Togodo South National Parks), 'Les Deux Bé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Similarly, another study (Atsri et al., 2020) reported that 60% of the buffer zone surrounding the FMNP is also now degraded, with agriculture, charcoal and firewood production cited as being the main drivers that detrimentally affect habitats. In addition, hunting activity (mostly targeting mammals, especially ungulates) has been reported in undisturbed and degraded areas of the FMNP buffer zone (Atsri et al., 2020), and illegal hunting activity (which is carried out to supply demand for bush meat, traditional medicine and the international exotic pet trade) has been reported within the boundaries of the National Park (Segniagbeto, Assou, et al., 2020). Globally, such anthropogenic influences are considered to have caused biodiversity loss, species and population extirpations and declines in local species abundance (IPBES, 2019), including other parts of the West African forest‐savannah mosaic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another study (Atsri et al., 2020) reported that 60% of the buffer zone surrounding the FMNP is also now degraded, with agriculture, charcoal and firewood production cited as being the main drivers that detrimentally affect habitats. In addition, hunting activity (mostly targeting mammals, especially ungulates) has been reported in undisturbed and degraded areas of the FMNP buffer zone (Atsri et al., 2020), and illegal hunting activity (which is carried out to supply demand for bush meat, traditional medicine and the international exotic pet trade) has been reported within the boundaries of the National Park (Segniagbeto, Assou, et al., 2020). Globally, such anthropogenic influences are considered to have caused biodiversity loss, species and population extirpations and declines in local species abundance (IPBES, 2019), including other parts of the West African forest‐savannah mosaic.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeable, from our survey is the absence of other threatened taxa such as the African lion (Vulnerable) and leopard (Vulnerable) both of which are currently considered as possibly extinct in Togo (Bauer et al, 2016). In addition, the absence of mona monkey (Near Threatened), lesser spot-nosed guenon (Near Threatened), white-thighed colobus monkey (Critically Endangered) and white-bellied pangolin (Phataginus tricuspis; Endangered) is noticeable given that these species have been previously reported from within the FMNP (Segniagbeto, Assou, et al, 2020;Segniagbeto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic investigations have shown that WBP consisted of six cryptic, geographically traceable lineages [9], one of which occurs ‘outside’ the rainforest blocks, in a West African savannah corridor interspersed with very fragmented forest cover, the Dahomey Gap[10]. The Dahomey Gap lineage (DGL) is of peculiar patrimonial importance as it is endemic to a unique biogeographical zone in western Africa (from Togo to Benin and southwestern Nigeria; [9] and likely is the only pangolin species surviving in the Dahomey Gap [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…DGL populations currently suffer from intense levels of deforestation and hunting. Populations are fragmented into –generally small– patches of forest islands, and have drastically decreased in abundance through the last decades [11, 12]. In Togo and Benin, WBG is hunted for its meat and use in traditional medicine, both contributing to its overexploitation [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation